Possibilities of Computer-supported Collaborative Learning in Blended-learning - Ulmane-Ozoliņa, Lāsma (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Higher education institutions in Latvia offer blended learning where traditional face to face lectures are combined with e-learning options. Research on blended learning in Latvia is very little. Author offers her view on blended learning analysis in Latvia and possibility to introduce computer-supported collaborative learning as tool to involve students in more active learning and learners’ community building. As theoretical background author uses sociocultural theory and participatory metaphor. Article describes several very important issues to put attention on when starting to introduce CSCL and blended learning in Latvia’s higher education institutions.